Microbial consortia enhance the yield of maize under sub-humid rainfed production system of India - Manjunath, Mallappa; Khokhar, Anil; Chary, Gajjala Ravindra; Singh, Manmohanjit; Yadav, Sushil Kumar; Gopinath, Kodigal A.; Jyothilakshmi, Narayana; Srinivas, Karlapudi; Prabhakar, Mathyam; Singh, Vinod Kumar (Frontiers in Sustainable Food Systems, 2023)
Plant beneficial microorganisms are being used to improve soil health and crop yield in different cropping systems. Maize is an important crop grown around the world for food, feed and raw material for various industries. In the present study, microbial consortia 1 (Pseudomonas putida P7 + Paenibacillus favisporus B30) and microbial consortia 2 (Pseudomonas putida P45 + Bacillus amyloliquefaciens B17) were tested under field conditions for their suitability in improving maize yield under rainfed situations at Ballowal Saunkhri (Punjab) having sub-humid (Hot Dry) climatic conditions. Pooled analysis of three years field experiments data showed that, seed + soil application of microbial consortia 1 and 2 led to enhancement in grain yield of kharif maize by 27.78 and 23.21 % respectively over uninoculated control. Likewise, significant increase in Benefit:Cost ratio as well as straw yield was also observed. The present investigation suggests that, microbial consortia would help in significantly improving the yield and economics of maize grown on inceptisols under rainfed conditions.